(untitled) (Journal of Hama University, 2021)
The Aim of this study Comparative between marginal microleakage of Class II cavities restored with bulk-fill resin and conventional composite resin Materials and Methods: class II cavities was prepared in 40 extracted human sound premolars were selected. The overall dimensions and depth of the cavities were standardized as follow:4 mm length occlusocervically, 3 mm width buccolingually and 2 mm depth axially, divided into two groups of 20. Group 1 incrementally filled with Tetric N Ceram .Group 2 was filled with Tetric-N-Ceram bulk-fill composite in one layer. The samples were thermocycled for 500 cycles between 5-55°C. The samples were incubated for 24 hours and then immersed in 1% methylene blue dye. All samples were mesiodistally sectioned and degree of microleakage scored under a light microscope. The data were analyzed using Mann Whitney test . The results showed significant difference among two groups In terms of microleakage,the microleakage in bulk – fill was more than conventional resin composite ,microleakage in occlusal margins was greater than that in gingival margins.